The Clinical Utility of the Seated Wall Angel as a Test with Scoring - Chad Kofoed; Allison Palmsten; Jonathon Diercks; Michael Obermeier; Marc Tompkins; Terese L Chmielewski (North American Sports Medicine Institute, 2024)
# Background The seated wall angel (SWA) is an intervention to improve upper quarter mobility but has not been described as a clinical test with scoring. # Hypothesis/ Purpose To explore the clinical utility of the SWA as a test with scoring. The authors hypothesized that SWA test scores would be lower on the injured than uninjured side, improve over time, and show stronger association with patient-reported shoulder function than shoulder mobility tests. # Study Design Prospective cohort. # Methods Patients diagnosed with anterior shoulder instability and referred to physical therapy participated. Testing occurred after physical therapy examination (initial) and six weeks later (follow-up). Rehabilitation was not controlled. Testing included clinical tests (SWA, passive shoulder external rotation range of motion, total arc of motion) and patient-reported outcomes including the American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form, (ASES) and the Western Ontario Shoulder Instability Index (WOSI). The SWA test was scored 0 to 3 points bilaterally based on number of body contacts with the wall (i.e., elbows and fingertips, posterior fingers, posterior forearm). Passive range of motion was measured with a standard goniometer. SWA scores were compared between sides at initial testing and compared between testing timepoints on the injured side. Associations among injured side clinical test values and patient-reported outcome scores were examined. # Results Mean (SD) SWA score on the injured side was significantly lower than the uninjured side at initial testing \[1.6 (1.0) vs 2.2 (1.1), p = 0.045] and significantly increased at follow-up testing \[2.4 (1.0), p = 0.041]. Only SWA test score was significantly correlated with ASES (r=0.597) and WOSI (r=-0.648) scores at initial testing, and SWA test score was significantly correlated with WOSI score at follow-up testing (r=-0.611). # Conclusions The clinical utility of the SWA test is supported by distinguishing the injured and uninjured sides and having stronger associations with patient-reported shoulder function than shoulder mobility tests.